Nota sobre la estructura del estrato arbóreo del bosque mesófilo de montaña en los alrededores del campamento "El Triunfo", Chiapas - Williams Linera, Guadalupe (Instituto de Ecología, A.C., 1991)
Tree stratum structure and floristic composition data of a cloud forest site located between 1850 and 2150 m of altitude in the Biosphere Resen/e “El Triunfo", Chiapas are presented and analyzed. Density (stems/ha) and basal area (m2/ha) of trees greater than 5 cm of diameter were 960 and 54.5, respectively;tree fern density was 150 individuals/ha. Trees are up to 40 m tall with diameters greater than 2 m. The dominant tree species are Matudaea trinervia, Quercus crispifolia, Hedyosmum mexicanum, Ocotea sp., Conostegia volcanalis, Amphitecna sp., and Symplococarpon aff. purpusii. The study site ¡s not representative of the cloud forest of the Reserve. It is important to carry out more floristic and ecological studies in order to relate the changes in vegetational associations to variations in altitude and topography.